(untitled) (Urdimento: Revista de Estudos em Artes Cênicas, 2021)
This article seeks to share the experiences produced in the intertwining of the disciplines Creation Laboratory: Corporal Research and Creation Laboratory: Corpographies, assumed respectively by Patrícia Caetano and Ana Mundim, in the graduation courses in Dance at the Federal University of Ceará. In the context of COVID-19’s sanitary crisis, remote emergency teaching of the respective disciplines occurred from the intersection of the somatic approach of Body-Mind Centering™ and the philosophical approach of Anthroposophy, providing opportunities for the development of creative works based on the relationship of the body with the four elements of nature in visual and/or audiovisual formats.